In vitro Modeling of Chicken Cecal Microbiota Ecology and Metabolism Using the PolyFermS Platform - Asare, Paul Tetteh; Greppi, Anna; Pennacchia, Alessia; Brenig, Katharina; Geirnaert, Annelies; Schwab, Clarissa; Stephan, Roger; Lacroix, Christophe (Frontiers in Microbiology, 2021)
Continuous in vitro fermentation models provide a useful tool for a fast, reproducible and direct assessment of treatment-related changes in microbiota metabolism and composition independent of the host. In this study, we used the PolyFermS model to mimic the conditions of the chicken caecum and evaluated three nutritive media for in vitro modelling of the chicken caecal microbiota ecology and metabolism. We observed that our model inoculated with immobilized caecal microbiota and fed with a modified Viande Levure medium (mVL-3) reached a high bacterial cell density of up to ca. 10.5 log cells per mL and stable microbiota composition, akin to the host, during 82 days of continuous operation. Relevant bacterial functional groups containing primary fibrolytic (Bacteroides, Bifidobacteriaceae, Ruminococcaceae), glycolytic (Enterococcus), mucolytic (Bacteroides), proteolytic (Bacteroides) and secondary acetate-utilizing butyrate-producing and propionate-producing (Lachnospiraceae) taxa were preserved in vitro. Besides, conserved metabolic and functional KEGG pathways were observed between in vitro microbiota and caecal inoculum microbiota as predicted by functional metagenomics analysis. Furthermore, we demonstrated that the continuous inoculation provided by the inoculum reactor (IR), generated reproducible metabolic profiles in second-stage reactors comparable to the chicken caecum, allowing for the simultaneous investigation and direct comparison of different treatments with a control. In conclusion, we showed that PolyFermS is a suitable model for mimicking chicken caecal microbiota fermentation allowing ethical and ex vivo screening of environmental factors, such as dietary additives, on chicken caecal fermentation. We report here for the first time a fermentation medium (mVL-3) that closely mimic the substrate conditions in the chicken caecum and support the growth and metabolic activity of the caecal bacterial akin to the host. Our PolyFermS chicken caecum model is a useful tool to study microbiota functionality and structure ex vivo.